DIGITAL TRANSFORMATION IN HIGHER EDUCATION: KEY TECHNOLOGIES, METHODS, AND DEVELOPMENT DIRECTIONS - Ubaydullayeva Sh. R.; Ismailov M. M. (Bright Mind Publishing, 2025)
Higher education today is undergoing profound changes associated with the active implementation of digital technologies. Universities are adapting their educational processes to new conditions, striving to make learning more flexible, personalized, and practice-oriented. The article examines the key directions of digital transformation, including the use of Artificial Intelligence, Virtual and Augmented Reality (VR/AR) technologies, online learning, EdTech platforms, multimodal approaches, and intelligent learning resources. The analysis shows that digital tools are changing not only the forms of teaching but the entire educational model, shifting the focus to active student participation, flexible trajectories, and adaptive methodologies. At the same time, universities face a number of challenges: the need for digital literacy development, data protection, ethical issues, and risks of the digital divide. The article presents conclusions and recommendations that may be useful to researchers, educators, and educational program developers.
Keywords: Digital transformation; higher education; artificial intelligence; VR/AR; EdTech; online learning; multimodal pedagogy; smart textbooks; adaptive learning.